Sentiment analysis – a review and agenda for future research in hospitality contexts - Ma, E.; Cheng, Mingming; Hsiao, A. (Emerald Group Publishing Limited, 2018)
Purpose: The study aims to provide a critical review of the origin, development and process of sentiment analysis (SA) and a demonstration for hospitality researchers and students on how to perform SA using a sample study. Design/methodology/approach: A critical review and sample case demonstration approach was applied. The sample study used Leximancer to perform SA using TripAdvisor review data. Findings: A critical evaluation of the most popular SA tools was provided, highlighting their advantages and disadvantages. A step-by-step demonstration with data provided makes it possible for readers to learn this technique at own pace. Originality/value: By providing a critical review of SA supported with a demonstration case study, this study makes a timely contribution for broader awareness and understanding, as well as the application of SA in hospitality.